Gestión administrativa y la calidad del servicio en la Unidad de Gestión Educativa Local Ucayali Contamana 2024 - Abisrror Huansi, Huber (2025)
The objective of this final project was to determine the relationship between administrative management and service quality at the Ucayali Contamana 2024 Local Education Management Unit. The project used fundamental, descriptive-correlational research with a non-experimental approach. A select group of 175 users was selected as our primary data source. According to the findings, 40% described administration as ordinary, while 36% equally valued service excellence. A close connection between administration and service excellence was determined, supported by a coefficient of 0.828 and a significance level of 0.000. Likewise, planning reveals a coefficient and significance of (r=0.703; p=0.000), structure exhibits (r=0.761; p=0.000), management exhibits (r=0.759; p=0.000), and control exhibits a coefficient and significance of (r=0.743; p=0.000). Service excellence at the Ucayali Contamana UGEL is based on these variables.